2022
DOI: 10.1101/2022.09.22.509027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Selection Landscape and Genetic Legacy of Ancient Eurasians

Abstract: Summary The Eurasian Holocene (beginning c. 12 thousand years ago) encompassed some of the most significant changes in human evolution, with far-reaching consequences for the dietary, physical and mental health of present-day populations. Using an imputed dataset of >1600 complete ancient genome sequences, and new computational methods for locating selection in time and space, we reconstructed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 148 publications
6
29
0
Order By: Relevance
“…First, recent genetic modifications in the modern-day human genome reveal a particular enrichment for psychiatric traits (e.g. depression, alcohol intake; see Figure 2 and Table S1), in line with recent evidence showing that introgressed variants from Neanderthals (variants relatively recent in human evolution, ∼50,000 years ago) are linked to smoking, alcohol consumption, and mood-related traits 49 ; and with findings of an overrepresentation of alleles conferring risk for mood-related traits specifically in the genomes of ancient farmers (∼11,000 years old), but not in the genomes of evolutionarily earlier hunter-gatherer 50 . Second, genetic variants associated with intelligence, educational attainment, hippocampal volume, and psychiatric disorders appear to have a more recent evolutionary age than expected considering their polygenicity and MAF, suggesting the potential action of selection pressures on these phenotypes (Supplementary Results, Table S2).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…First, recent genetic modifications in the modern-day human genome reveal a particular enrichment for psychiatric traits (e.g. depression, alcohol intake; see Figure 2 and Table S1), in line with recent evidence showing that introgressed variants from Neanderthals (variants relatively recent in human evolution, ∼50,000 years ago) are linked to smoking, alcohol consumption, and mood-related traits 49 ; and with findings of an overrepresentation of alleles conferring risk for mood-related traits specifically in the genomes of ancient farmers (∼11,000 years old), but not in the genomes of evolutionarily earlier hunter-gatherer 50 . Second, genetic variants associated with intelligence, educational attainment, hippocampal volume, and psychiatric disorders appear to have a more recent evolutionary age than expected considering their polygenicity and MAF, suggesting the potential action of selection pressures on these phenotypes (Supplementary Results, Table S2).…”
Section: Discussionsupporting
confidence: 87%
“…Second, recent genetic modifications in the modern-day human genome reveal a particular enrichment for psychiatric traits (e.g. depression, alcohol intake; SI Appendix), in line with recent evidence showing that introgressed variants from Neanderthals (variants relatively recent in human evolution) are linked to smoking, alcohol consumption, and mood-related traits (48); and with findings of an overrepresentation of alleles conferring risk for mood-related traits specifically in ancient farmers genome (~11,000 years old) but not in evolutionary previous hunter-gatherer genome (49). Third, genes related to neuropsychiatric conditions (SCZ, BD, and AD) were found to contain more recent genetic modifications compared to other genes.…”
Section: Discussionsupporting
confidence: 83%
“…We recover approximately 20 candidate loci, including for example LCT [18], the gene encoding the lactase enzyme, and the HLA region, both known to have been under recent positive selection in Europeans (Figure 4b). The peak at chromosome 12 falls inside HECTD4, which has recently been found to be under selection in Eurasians [13], though we note that the credible interval contains other genes.…”
Section: Resultsmentioning
confidence: 73%
“…Previous studies of natural selection in the European Neolithic have either compared allele frequencies or haplotype structure with other ancient and modern populations. 5 , 11 14 However, no study to date has specifically attempted to identify adaptive admixture, despite the fact that this mode of adaptation has been repeatedly observed in humans. A recent study identified two optimal approaches to detect adaptive admixture in data from present-day populations, based on allele frequencies and local ancestry.…”
Section: Resultsmentioning
confidence: 99%
“…We note that the HLA appears to be a frequent target of natural selection and the processes described above are not exclusive. Extensive evidence of selection has been detected both in scans focusing on the past few millennia, 5 , 11 , 14 , 52 , 58 and following introgression from archaic humans. 54 , 59 Future studies, including whole-genome shotgun data in tandem with improved functional annotation, may shed further light on this adaptive process.…”
Section: Resultsmentioning
confidence: 99%